Perfil clínico das crianças com cardiopatias congênitas associadas a síndromes assistidas num ambulatório de referência - Ferreira, Camila Batista (2018)
Congenital heart disease (CHD) is one of the most common birth defects. It is known that chromosomal abnormalities, Mendelian disorders and associations of malformation may be present in patients with HCV. Extracardiac malformations may present a higher risk of morbidity and mortality in these children with HCV. Clarifying which defects and syndromes are associated with CHD is an essential tool for assessing appropriate management, determining the risks of recurrence, and guiding expectations for the effectiveness of prevention and treatment strategies. This is a retrospective study in which records of children and adolescents with genetic syndromes attended at the pediatric cardiology outpatient clinic of the Federal University Hospital of Sergipe were analyzed. A total of 345 records were evaluated, of which 37.6% had syndromes and 46% had congenital heart diseases. The most commonly found syndrome was Down's syndrome, being associated with atrioventricular septal defects, CIA, CIV, PCA, heart diseases that have been associated with this syndrome in previous studies. The second most common syndrome and the one that most strengthened the information collected in the literary review was Marfan syndrome, since most of them are carriers of Mitral Valve Prolapse.